Comparison of Serum Adiponectin in Patients with Psoriasis and Healthy Controls: A Cross-sectional Study - Diana Mariam; Sibiya Odayappurath; Rosmi Johnachan (Journal of Clinical and Diagnostic Research)
Introduction: Psoriasis, a chronic inflammatory skin condition, is increasingly recognised as a systemic illness due to its associations with obesity, dyslipidaemia, insulin resistance, Metabolic Syndrome (MetS), and cardiovascular disorders. Adipocytes produce the insulin-sensitising and anti-inflammatory hormone adiponectin, which is linked to metabolic homeostasis and may serve as a biomarker for metabolic disorders associated with psoriasis. Aim: To evaluate serum adiponectin levels in psoriasis patients compared to healthy controls and analyse its relationship with metabolic parameters. Materials and Methods: The present comparative cross-sectional study was conducted at Government Medical College, Kozhikode, Kerala, India from June 2018 to June 2019. The study included 40 psoriasis patients (age 18-65 years) and 40 age and sex matched healthy controls. The lipid profile, serum adiponectin levels, anthropometric characteristics, and Fasting Blood Sugar (FBS) were measured. Psoriasis patients were further assessed for MetS using the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Spearman’s correlation analysis was used to examine relationships between adiponectin levels and metabolic markers. Group comparisons were performed using the Chi-square and Mann-Whitney U tests, with significance set at p-value <0.05. Results: The mean age of psoriasis patients was 46.0±12.0 years, compared to 40.9±9.8 years in controls. Women comprised 62.5% of cases and 80.0% of controls. Serum adiponectin levels were significantly lower in psoriasis patients (15.81±5.76 ng/mL) than in controls (23.10±8.06 ng/mL; p-value <0.001). Psoriasis patients also had significantly higher Waist Circumference (WC) (98.20±8.33 vs. 92.00±12.66 cm; p-value=0.03) and FBS (107.90±27.61 vs. 89.10±5.90 mg/dL; p-value <0.01). Adiponectin showed weak negative correlations with FBS and BMI (rho=–0.22; p-value=0.18). MetS was present in 75% of cases. Conclusion: Reduced adiponectin levels in psoriasis patients, particularly those with MetS, highlight its potential as a biomarker for metabolic dysfunction. Targeting adiponectin pathways may help mitigate psoriasis-associated metabolic complications.